Teknik Pemeriksaan Kedokteran Nuklir Bone Scan di Instalasi Radiologi RSUP Dr. Kariadi Semarang - Nanik Sudaryatmi; Siti Masrochah; Muhammad Erfansyah (Poltekkes Kemenkes Semarang, 2021)
Background: A bone scan or commonly referred to as bone print is nuclear medicine examination using a radioactive substance or radiopharmaceutical that is inserted into the body through intravenous injection which aims to help diagnose abnormalities that occur in the bone. This imaging procedure uses a radiopharmaceutical 99mTc-MDP (methylenediphosphonate) is the most commonly used radiopharmaceutical.Methods: The patient will be injected with this radiopharmaceutical at a dose of 15-20 mCi, through the vein in the hand. Imaging can be done as soon as the radiopharmaceutical is injected or after a while to wait for the radiopharmaceutical to be distributed and absorbed by the bone, about 3-5 hours later. Imaging is done by three-phase method, namely the first phase (Vascular phase), the second phase (Blood Pool phase), and the third phase (Total body phase) l.Results: The bone scan method is an efficient examination because in 1x the imaging can provide a complete picture from the head to the foot. Evaluation of results, under normal conditions the distribution of radioactivity in the bone appears symmetrical.Conclusion: In the process of bone metastasis, it can be seen that typical pathological radioactivity can be multiple (multiple hot spots). Malignant tumors can be distinguished from benign tumors by blood pool examination.